Makna Tentang Berpuasa (Studi Eksegetis Yesaya 58:1-12) dan Implikasinya Bagi Orang Kristen Masa Kini - Dosma Arihta Berutu (Jurnal Teologi Injili dan Pendidikan Agama, 2023)
Fasting should not only be considered as a mere ritual act, but should have a concrete form that means carrying out an act of liberating justice. Fasting is voluntary abstinence from food in order to achieve a certain goal. or also add abstinence from eating and drinking. This research aims to find out the meaning of fasting according to Isaiah 58:1-12 and its implications in the lives of Christians today. The research method in this scientific work is a qualitative method with a descriptive approach. From the results of the Exegetical study of Isaiah 58:1-12, increasing social awareness and giving more attention to others, especially to those who are less fortunate or in need. Through fasting, Christians can draw closer to God and experience closer bonds with others.